School meals in Slovenia and some European countries - Poličnik, Rok; Benko, Borut; Simčič, Irena; Farkaš Lainščak, Jerneja (Anali PAZU, 2022)
Offering healthy and balanced meals in schools, in addition to educating and raising children’s awareness on the importance of healthy nutrition, is an important public health measure. The article presents a description of the organized school meals system in Slovenia and a comparison with thirteen European countries. Slovenia is one of the countries with over seventy-year old tradition of school meals. The field is regulated by law, whereas educational institutions are provided with human, financial and spatial resources, which enable planning, preparation and distribution of school meals. The arrangements and approaches to providing meals during school hours vary from country to country in Europe and depend on various factors. Most countries have a decentralized arrangement where the responsibility for providing school meals is transferred to the founder (local community) and the educational institution. Slovenia is a country that, in addition to the comprehensive organization of the measure of school meals and subsidies for meals, also has a legally regulated professional monitoring with counselling, which is systematically coordinated throughout the country by the National Institute of Public Health.
Keywords: school meals; school lunch; diet; primary school; children and adolescents